1997
DOI: 10.1073/pnas.94.17.8939
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated inhibition of the growth of larvae from an insect causing cutaneous myiasis in a mammalian host

Abstract: Many insects feed on blood or tissue from mammalian hosts. One potential strategy for the control of these insects is to vaccinate the host with antigens derived from the insect. The larvae of the f ly Lucilia cuprina feed on ovine tissue and tissue f luids causing a cutaneous myiasis associated with considerable host morbidity and mortality. A candidate vaccine antigen, peritrophin 95, was purified from the peritrophic membrane, which lines the gut of these larvae. Serum from sheep vaccinated with peritrophin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 29 publications
(28 reference statements)
0
42
0
1
Order By: Relevance
“…A number of PM proteins may be associated with this process and a few of them have the chitin-binding activity. The activity was attributed to their peritrophin domains (Elvin et al, 1996;Casu et al, 1997;Schorderet et al, 1998;Tellam et al, 1999;Wijffels et al, 2001;Tellam et al, 2003). In this study, we identified two chitin-binding proteins, BmPM-P43 and BmPM-P41, containing a polysaccharide deacetylase domain, different from the proteins containing peritrophin domains.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A number of PM proteins may be associated with this process and a few of them have the chitin-binding activity. The activity was attributed to their peritrophin domains (Elvin et al, 1996;Casu et al, 1997;Schorderet et al, 1998;Tellam et al, 1999;Wijffels et al, 2001;Tellam et al, 2003). In this study, we identified two chitin-binding proteins, BmPM-P43 and BmPM-P41, containing a polysaccharide deacetylase domain, different from the proteins containing peritrophin domains.…”
Section: Discussionmentioning
confidence: 77%
“…Several peritrophins were identified: Peritrophin-44 and peritrophin-48 were purified from 6 M urea extract of Lucilia cuprina PM (Elvin et al, 1996;Schorderet et al, 1998); Ag-Aper1, from blood-fed adult female Anopheles gambiae (Shen and Jacobs-Lorena, 1998); Peritrophin-95 be purified from L. cuprina (Casu et al, 1997) etc. These PM proteins have the peritrophin domains, which contain 65-70 amino acid residues and are characterized by a conserved register of six cysteine residues C-X 13-20 CX 5-6 CX 9-19 -CX 10-14 CX 4-14 C (X is not cysteine) called the peritrophin-A domain and a few aromatic amino acid residues .…”
Section: Introductionmentioning
confidence: 99%
“…The peritrophic matrix is an extracellular sac, composed of chitin, proteins, and proteoglycans (2,3), which completely surrounds the ingested food and is secreted by the gut epithelial cells. All the recently cloned peritrophic matrix proteins from Lucilia cuprina (5,6), Trichoplusia ni (7), and the mosquito Anopheles gambiae (8) have at least two chitinbinding domains that are presumed to function in the crosslinking of the chitin fibrils. However, some of these proteins also have mucin-like domains (6,7), suggesting that the insect peritrophic matrix resembles the vertebrate intestinal mucus, a structure largely composed of mucins.…”
mentioning
confidence: 99%
“…All the recently cloned peritrophic matrix proteins from Lucilia cuprina (5,6), Trichoplusia ni (7), and the mosquito Anopheles gambiae (8) have at least two chitinbinding domains that are presumed to function in the crosslinking of the chitin fibrils. However, some of these proteins also have mucin-like domains (6,7), suggesting that the insect peritrophic matrix resembles the vertebrate intestinal mucus, a structure largely composed of mucins. In addition to providing protection, the peritrophic matrix may also facilitate digestion by compartmentalization of digestive enzymes (9).…”
mentioning
confidence: 99%
“…Resistance factors deployed, or considered for use, in host-plant resistance include Bt -endotoxin, protease inhibitors, -amylase inhibitors (Shade et al, 1994), Photorhabdus luminescens proteins (Roush, 1998), Helicoverpa stunt virus (Schuler et al, 1998), antibodies (Casu et al, 1997), and lectins (Pittendrigh et al, 1997;ZhuSalzman et al, 1998). Some of aforementioned resistance factors are currently in the process of being developed for transformation into plants.…”
Section: Potential Toxins For Testing Ncr Strategiesmentioning
confidence: 98%